A large‐area CMOS detector for high‐energy synchrotron powder diffraction and total scattering experiments. (4th February 2014) - Abdala, Paula Macarena; Mauroy, Henrik; van Beek, Wouter
<x xml:space="preserve">Abstract</x> A complementary metal‐oxide semiconductor (CMOS) detector with an active area of 290.8 × 229.8 mm has been evaluated for X‐ray scattering experiments at energies between 20 and 50 keV. Detector calibration and integration procedures are discussed in addition to the determination of the linearity, angular resolution and energy response of the detector in the context of its envisaged use. Data on reference compounds and samples with different crystallinity were collected and analysed with classical Rietveld and pair distribution function refinements. Comparisons with literature and high‐resolution data from the same beamline demonstrate that the presented detector is suitable for crystallographic and total scattering experiments.